A conceptual model for measuring the competency level of Small and Medium-sized Enterprises (SMEs) - ÖZTEMEL, ERCAN; ÖZEL, SEMİH (UNIV MARIBOR, FAC MECHANICAL ENGINEERING, 2021)
Small and Medium-Sized Enterprises (SMEs) are of major importance to developing countries. SMEs are the main drivers to strengthen society in sustaining economic growth and development. Governments provide various support programs to improve their industrial power and to increase the number of enterprises in the market. The enterprises must be assessed and suitable funds should be provided to those in need, to achieve an effective support program in the most efficient way. This requires implementing an assessment methodology based on a predefined set of scientific criteria. The current literature is comprehensive enough to assess the healthiness of the enterprises concerning strategic, technologic, financial as well as intellectual competencies but on the other hand, it lacks of an assessment model. This study aims to introduce a general framework for sustaining an effective assessment methodology for SMEs to eliminate this gap. The proposed model measures five different types of competencies such as Technological Competency, Strategic Competency, Financial Competency, Intellectual Competency, R&D and Innovation Competency. These competencies are to put forth the conditions in which the enterprises are running accurately. A real-life case study is conducted to ensure the baseline of the model to be implemented. The governmental organizations may utilize the model for sustaining their support role effectively to SMEs.
Keywords: Small and medium-sized enterprises (SMEs); Competency assessment; Technological competency; Strategic competency; Financial competency; Intellectual competency; R&D and innovation competency; Smart manufacturing; Industry 4.0